Style Manuals of the English-Speaking World : A Guide - Howell, John Bruce (Oryx Press, 1983)
This is a guide to style manuals and author's guides from the English-language publishing communities of Australia, Canada, India, New Zealand, Nigeria, Pakistan, Papua New Guinea, the Philippines, the United Kingdom, the United States, and Zimbabwe.